2017
DOI: 10.1177/1049732317707726
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Touch in Health Care: A Meta-Ethnography Across the Health Care Professions

Abstract: Touch mediates health professionals' interactions with patients. Different professionals have reported their practices but what is currently lacking is a well-theorized, interprofessional synthesis. We systematically searched eight databases, identified 41 studies in seven professions-nursing (27), medicine (4), physiotherapy (5), osteopathy (1), counseling (2), psychotherapy (1), dentistry (1)-and completed a meta-ethnographic line-of-argument synthesis. This found that touch is caring, exercises power, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 79 publications
3
74
0
1
Order By: Relevance
“…Kelly et al. used meta‐ethnography to systematically review research publications on touch and identified three themes: (i) touch communicates care and is a form of interaction beyond words; (ii) touch crosses boundaries and therefore needs safe spaces that are negotiated; and (iii) touching exercises power, being linked to status – although health professionals like to initiate touch, they are less comfortable when touch is reciprocated . Pedrazza et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kelly et al. used meta‐ethnography to systematically review research publications on touch and identified three themes: (i) touch communicates care and is a form of interaction beyond words; (ii) touch crosses boundaries and therefore needs safe spaces that are negotiated; and (iii) touching exercises power, being linked to status – although health professionals like to initiate touch, they are less comfortable when touch is reciprocated . Pedrazza et al.…”
Section: Resultsmentioning
confidence: 99%
“…The quantity and depth of literature on touch are most pronounced for nursing, although there is also some research in medicine, occupational therapy, and physical therapy. 5 For the nursing profession, physical touch has been categorised as having the following functions: task focused; to orientate; to express emotion; instrumental; protection; to show interest in another; alleviation of pain and/or fear; and to massage. 6 More holistically, touch has been conceptualised phenomenologically and explored through the lived experiences of those who touch and are touched.…”
Section: Conceptualising Touchmentioning
confidence: 99%
See 2 more Smart Citations
“…In many body-oriented therapies, like physiotherapy, different types of physical touch are an essential part of the treatment practice and the instruction of specific therapeutic movement exercises (Roger et al, 2002). Although the particular way of touching patients is assigned great importance in physiotherapy education and training (Roger et al, 2002;Nicholls and Holmes, 2012;Bjorbaekmo and Mengshoel, 2016;Kelly et al, 2018), this aspect is not examined in research on instructional exercise videos. Little is known about how the use of therapeutic touch in exercise videos affects viewers' perceptions of the instructor and their own contribution to treatment success.…”
Section: Introductionmentioning
confidence: 99%